2006
DOI: 10.2109/jcersj.114.524
|View full text |Cite
|
Sign up to set email alerts
|

Polymer-Derived SiBCN Ceramic and their Potential Application for High Temperature Membranes Dedicated to Prof. Dr.-Ing. Dr.h.c. Hartmut Fuess on the occasion of his 65th birthday

Abstract: A novel preceramic polymer suitable to form a SiBCN ceramic was synthesized by hydroboration reaction of 1,3,5-trivinyl-1,3,5-trimethyl-cyclotrisilazane with borane dimethylsulphide. The obtained polymer denoted as polyborosilazane was characterised by FT-IR and NMR spectroscopy and its thermal stability was studied by thermal gravimetric analysis in combination with in situ mass spectrometry TGMS. The polymer-to-ceramic transformation was achieved at 1050c C in inert argon atmosphere yielding black and X-ray … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
31
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 33 publications
1
31
0
Order By: Relevance
“…[3][4][5] It has been shown that PDCs remain stable up to 1400-1500 • C and, in special cases, even at 2000 • C. 6 The PDCs have been shown to hold promise for high temperature membranes, oxidation resistant coatings, and flux sensors for gas turbine engines. [7][8][9] In addition to their structural properties and chemical stability, the PDCs also possess functional properties of different kinds. They are semiconductors at least up to 1300 • C. 10 Though amorphous, they are intensely photoluminescent 11 with a wide spectrum emission.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] It has been shown that PDCs remain stable up to 1400-1500 • C and, in special cases, even at 2000 • C. 6 The PDCs have been shown to hold promise for high temperature membranes, oxidation resistant coatings, and flux sensors for gas turbine engines. [7][8][9] In addition to their structural properties and chemical stability, the PDCs also possess functional properties of different kinds. They are semiconductors at least up to 1300 • C. 10 Though amorphous, they are intensely photoluminescent 11 with a wide spectrum emission.…”
Section: Introductionmentioning
confidence: 99%
“…Micro and mesoporous structure formation through the polymer-derived ceramics (PDCs) [1,2] route has received increasing attention as an attractive ceramic processing route to develop gas separation membranes, gas sorbents and catalysts with thermally and/or chemically stable amorphous systems such as silicon nitride [3], silicon carbide [4,5,6,7,8,9], silicon carbonitride (Si–C–N) [10], silicon oxycarbide (Si–O–C) [11,12,13], silicon oxycarbonitride (Si–O–C–N) [14,15,16] and other quaternary Si–M–C–N (M=B, [17,18], Ni [19]). During the crosslinking and subsequent high-temperature pyrolysis of polymer precursors, by-product gases such as CO 2 , CH 4 , NH 3 and H 2 were detected, and the microporosity in the amorphous PDCs could be assigned to the release of the small gaseous species formed in-situ [14,15,16,20,21,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, micro and mesoporous structure formations have been often discussed for the polymer-derived amorphous silicon nitride [7,8], silicon carbide [9][10][11][12][13][14], silicon carbonitride (Si-C-N) [15], silicon oxycarbide (Si-O-C) [16][17][18] and quaternary Si-M-C-N (M = B [19,20], Ni [21]). During the crosslinking and subsequent high-temperature pyrolysis under an inert atmosphere of polymer precursors, by-product gases such as CH 4 , NH 3 and H 2 were detected [5,22], and the microporosity in the polymer-derived non-oxide amorphous ceramics could be assigned to the release of the small gaseous species formed in-situ [8,22].…”
Section: Introductionmentioning
confidence: 99%